Aging of the immune system: Focus on inflammation and vaccination. Issue 10 (October 2016) - Pinti, Marcello; Appay, Victor; Campisi, Judith; Frasca, Daniela; Fülöp, Tamas; Sauce, Delphine; Larbi, Anis; Weinberger, Birgit; Cossarizza, Andrea
Abstract : Aging of the immune system is characterized a profound change in the functionality of both innate and adaptive immune system, and accompanied by the onset of a chronic, low‐grade inflammatory status, and by a reduced capability to trigger an effective response to vaccine, which is typical of elderly people. N = Neutrophils; M = monocytes/macrophages; DC = dendritic cells; LC = Langerhans' cells; NK = natural killer cells; T = T cells; B = B cells: Abstract : Major advances in preventing, delaying, or curing individual pathologies are responsible for an increasingly long life span in the developed parts of our planet, and indeed reaching eight to nine decades of life is nowadays extremely frequent. However, medical and sanitary advances have not prevented or delayed the underlying cause of the disparate pathologies occurring in the elderly: aging itself. The identification of the basis of the aging processes that drives the multiple pathologies and loss of function typical of older individuals is a major challenge in current aging research. Among the possible causes, an impairment of the immune system plays a major role, and indeed numerous studies have described immunological changes which occur with age. Far from the intention of being exhaustive, this review will focus on recent advances and views on the role that modifications of cell signalling and remodelling of the immune response play during human aging and longevity, paying particular attention to phenomena which are linked to the so called inflammaging process, such as dysregulation of innate immunity, altered T‐cell or B‐cell maturation and differentiation, as well as to the implications of immune aging for vaccination strategies in the elderly.